INOVASI HIJAB MENJADI LEBIH TRENDY DAN WUDHU FRIENDLY - Retno Hastuti; Bella Febriantikaningrum; Septiana Pidya Nugraheni; Erfa Saodah Rizqil Amin; Nia Sarinastiti (Universitas Pembangunan Nasional Veteran Yogyakarta, 2019)
In the development of the hijab trend model in this modern era there are many different types of hijabs, just aurat, here we innovate the